Phenotypic Variation and RAPD Polymorphism of Pisang Kepok Local Cultivars (Musa acuminata x Musa balbisiana, ABB, Saba Subgroup) - Wahyudi, Didik; Ilmi, Zahrobatul Lil; Hapsari, Lia (Universitas Brawijaya, 2022)
Pisang Kepok is a major local banana cultivar in Indonesia with high economic, social and cultural value. Particularly on the island of Java, there are several variations of Pisang Kepok recognised with their own local names, which makes difficulties in taxonomic identification and grouping. Morphological features are used in conventional banana cultivar classification, but they are deemed less precise due to their subjectivity, thus, it is supposed to be complemented with a molecular approach. This study aims to identify the phenotypic variation of Pisang Kepok local cultivars also their genetic polymorphism using Random Amplified Polymorphic DNA marker. Phenotypic variation was observed using 35 morphological characters. Six RAPD primers were used, i.e. OPA2, OPA3, OPA4, OPA11, OPA12, and OPA18. Clustering analysis, both phenotypic and genetic were performed using PAST v4.02. The morphological characterisation identified four variants of Pisang Kepok i.e. Kepok Abang, Kepok Putih, Kepok Manurun, and Kepok Australi; which all confirmed as ABB genome group. Phenotypic clustering showed that Pisang Kepok cultivars were separated into 3 clusters based on their local name, with a high similarity value of >90%. PCA biplot showed that the fruit flesh colour was the most important character contributed to the cultivar variation. RAPD marker also showed that each specimen was grouped according to its local name and source, with a similarity value of >80%. Both morphology and molecular (RAPD) markers resulted in the branching of Pisang Kepok which was closer to Pisang Klutuk than Pisang Barlin.